2017
DOI: 10.1371/journal.pone.0174985
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of duodenal epithelial neoplasms: Focus on tumors with a gastric mucin phenotype (pyloric gland-type tumors)

Abstract: ObjectiveEpithelial tumors less commonly occur in the duodenum than in the stomach or large intestine. The clinicopathological characteristics of duodenal epithelial tumors remain a matter of debate. We therefore studied resected specimens to investigate the clinicopathological characteristics of duodenal epithelial tumors.Materials and methodsAmong duodenal epithelial tumors resected endoscopically or surgically in our hospital, we studied the clinicopathological characteristics of 110 adenomas or intramucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 26 publications
6
56
0
Order By: Relevance
“…However, this finding was not statistically significant. Categorization according to phenotype was found to be necessary because a higher rate of malignancy was observed in G‐type NADETs, suggesting a more aggressive behavior than I‐type NADETs . As reported by Ushiku et al and Xue et al , G‐type cases demonstrated a poor prognosis since most cases involved advanced cancers .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, this finding was not statistically significant. Categorization according to phenotype was found to be necessary because a higher rate of malignancy was observed in G‐type NADETs, suggesting a more aggressive behavior than I‐type NADETs . As reported by Ushiku et al and Xue et al , G‐type cases demonstrated a poor prognosis since most cases involved advanced cancers .…”
Section: Discussionmentioning
confidence: 87%
“…Another strong point of our study was that the population included submucosal cancers. Mitsuishi et al and Toba et al reported clinicopathological features of NADETs, and mentioned the malignant potential of G‐type NADETs . However, there were few cases of submucosal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These reports showed that NADETs of the gastric type have higher malignant potential than those of the intestinal type [14-15]. It has also been shown that the intestinal type is associated with a more favorable disease course, with a longer survival when compared with the other types [16].…”
Section: Introductionmentioning
confidence: 99%